2009
DOI: 10.2147/ijwr.s4600
|View full text |Cite
|
Sign up to set email alerts
|

Major factors influencing antioxidant contents and antioxidant activity in grapes and wines

Abstract: Phenolic compounds in wines, especially in red wines, possess strong antioxidant activity, have the largest effect in decreasing atherosclerosis by both hypolipemic and antioxidant mechanisms. The long-term uptake of red wine has a positive impact on antioxidant activity (AA) of blood plasma in rats in vivo and increases AA by 15%-20% compared to a control group. In the article the effect of total phenolics (TP), total anthocyanins (TA), individual anthocyanins, procyanidins and phenolics contained in red grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 129 publications
6
40
1
5
Order By: Relevance
“…On the other hand, following the results of Kondrashov et al (2009), a significant positive relationship between TAC and TPC values was indicated in 6 Cabernet Sauvignon and 4 Merlot wines. The relatively constant total polyphenol content in our results is in accordance with results of Lachman et al (2009) suggesting the relevance of qualitative changes of phenolics. By evaluation of TPC and TAC relationships only a weak dependence was confirmed in Torysa variety (R² = 0.7427), while for the varieties Alibernet and Cabernet Sauvignon no conclusive correlation between the tested TPC and TAC values was found.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…On the other hand, following the results of Kondrashov et al (2009), a significant positive relationship between TAC and TPC values was indicated in 6 Cabernet Sauvignon and 4 Merlot wines. The relatively constant total polyphenol content in our results is in accordance with results of Lachman et al (2009) suggesting the relevance of qualitative changes of phenolics. By evaluation of TPC and TAC relationships only a weak dependence was confirmed in Torysa variety (R² = 0.7427), while for the varieties Alibernet and Cabernet Sauvignon no conclusive correlation between the tested TPC and TAC values was found.…”
Section: Resultssupporting
confidence: 92%
“…The analysis has shown that in almost all observed parameters the measured values were significantly higher in the varieties with dark-coloured skin and also flesh, in contrast to AA of the Cabernet Sauvignon variety, which has the dark-coloured skin, but the flesh is translucent. This phenomenon can be explained by the substances responsible for AA, which are largely presented mainly in the skin, which was also confirmed by Lachman et al (2009), where the decrease was caused mainly by condensation reactions of flavanols.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Because seed flour did not contain transresveratrol and the concentration in skin flour from 'Italian Riesling' is low, it might be possible that the compound did not rich the detection limit in the mixed flour of the same variety. Lachman et al (2009), also observed that transresveratrol in the must was mainly below the detectable limit.…”
Section: Total Anthocyanins Content (Tac)mentioning
confidence: 86%